2012
DOI: 10.1136/bmjopen-2011-000648
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between black tea consumption and key health indicators in the world: an ecological study

Abstract: ObjectivesThe aim of this study was to investigate potential statistical relationships between black tea consumption and key health indicators in the world. The research question is: Does tea consumption is correlated with one or more epidemiological indicators?DesignEcological study using a systematic data-mining approach in which the unit of the analysis is a population of one country.SettingSix variables, black tea consumption data and prevalence data of respiratory diseases, infectious diseases, cancer, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…While consumption of tea in the USA is among the lowest in the world [1], the USA is unique for its large consumption of iced tea, prepared at home or sold as canned or bottled beverages. According to the Tea Association of the USA the canned/bottled tea segment comprised just under 50% of the market share in 2016, with bagged/loose leaf tea comprising approximately 23% market share [50].…”
Section: Introductionmentioning
confidence: 99%
“…While consumption of tea in the USA is among the lowest in the world [1], the USA is unique for its large consumption of iced tea, prepared at home or sold as canned or bottled beverages. According to the Tea Association of the USA the canned/bottled tea segment comprised just under 50% of the market share in 2016, with bagged/loose leaf tea comprising approximately 23% market share [50].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have surveyed risks and benefits of these three drinks. Some studies have indicated that tea or coffee improve some diseases [cardiovascular disease, type II diabetes, certain cancers, such as prostate cancer and skin cancer, liver cirrhosis, Parkinson's and Alzheimer diseases, depression and anxiety Abel [7,[17][18][19][20][21] and some have suggested the opposite Onuegbu [22] and Zhu et al [23,24]. In this study we aimed to find out whether there is a relationship between these three drinks with depression and anxiety or not.…”
Section: Introductionmentioning
confidence: 99%
“…7 Whereas green tea contains mainly flavanols or catechins of epigallocatechin gallate (EGCG), epigallocatechin (EGC), epicatechin gallate (ECG), and epicatechin (EC); black tea is improved with complex flavonoides called theaflavins and thearubigins. 7,9,14,15 Moreover, quality and composition of the tea differs based on regional and environmental factors, such as Assamese tea (Camellia sinensis var. assamica), predominantly produced in South Asia, and contains much more polyphenol than oriental tea.…”
mentioning
confidence: 99%